Resolusi Konflik Berbasis Kearifan Lokal di Aceh: Studi tentang Eksistensi dan Peran Lembaga Adat dalam Membangun Perdamaian di Kota Lhokseumawe - Fajri M. Kasim; Abidin Nurdin (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2016)
This study examines the conflict resolution based on local wisdom in Aceh, focusing on the existence and role of traditional institutions in building peace and a frame of reference in banning conflicts in the city of Lhokseumawe. Local wisdom can be a resolution of the conflicts in society on the one hand, while on the other hand, it can bring a better impact than the formal justice. Local wisdom is laden with religious values that become a way of life of the Acehnese, ss mentioned in hadih majah (Aceh proverb): hukom ngon adat lagee zat ngon sifeut (religion and customs like substance and nature, in which they can not be separated.) This tradition is a very democratic conflict resolution without bloodshed between the two sides of the conflict, both vertically and horizontally. This research was conducted in the city Lhoksumawe using a qualitative approach and analyzed with the theory of structural functionalism. In this regard, we undertake the data collection method: in-depth interviews, focus group discussions (FGD), and document research. The results show that local wisdom still exists to resolve conflicts or disputes in society, such fighting between residents, lightweight theft (stealing) and land boundaries. While the role of traditional institutions in resolving conflicts or disputes is significant, and such traditional institutions, among others are: keuchik, tuha peut, imeum meunasah and other public figures.